ChemInform Abstract: Concise Synthesis of Rare Pyrido[1, 2‐a]pyrimidin‐2‐ones and Related Nitrogen‐Rich Bicyclic Scaffolds with a Ring‐Junction Nitrogen. Issue 20 (April 2016) - Alanine, T. A.; Galloway, W. R. J. D.; Bartlett, S.; Ciardiello, J. J.; McGuire, T. M.; Spring, D. R.
Abstract: A new and modular strategy for the concise synthesis of the title pyridopyrimidine derivatives and related compounds, derivatives of pharmaceutical interest, is developed.